Inhibitor-Immunology-Study - Wieland, I.; Wermes, C.; Eifrig, B.; Holstein, K.; Pollmann, H.; Siegmund, B.; Bidlingmaier, C.; Kurnik, K.; Nimtz-Talaska, A.; Niekrens, C.; Eisert, R.; Tiede, A.; Ebenebe, C.; Lakomek, M.; Hoy, L.; Welte, K.; Sykora, K.-W. (Hämostaseologie, 2008)
The development of inhibitors is one of the most important complications of replacement therapy in haemophilia, affecting mortality and morbidity. Inhibitor development is based on complex immunological factors. Cytokines and their receptors, T-cell receptors, and the Major Histocompatibility Complex may play important roles in the development of inhibitors. Earlier studies showed non significant associations between HLA class and inhibitor development. Later studies found an increased risk of inhibitor development if there was a combination between certain factor VIII mutations and HLA antigens. We performed HLA typing in 50 patients with haemophilia A in an effort to find associations with inhibitor development. Results: 25 patients had developed an inhibitor (11 low titre, 14 high titre), and 25 never had. In logistic regression analysis, HLA-A 34, DRB1 0405, DRB1 1301 seemed to be involved in inhibitor development and HLA-A 30, B 13, B15, B 57, Cw 12, DQB1 0303, DPB1 0201 protection against inhibitor development. In our patients, the HLA-associations with inhibitor development were different from those in previous publications.
Keywords: Haemophilia; inhibitor; HLA